Investigação estrutural de filmes finos de Ti1-xAlxN depositados por magnetron sputtering reativo - Dias, Iago Lemos (2024)
Ti1-xAlxN thin films with different Al contents (20, 40 and 60 at.%) were deposited by reactive magnetron sputtering with the aim of studying the structure in which the films are presented, evaluating whether there is formation of a Ti1-xAlxN solid solution or if there is only the presence of two binary nitrides TiN + AlN. The SEM-FEG, nanohardness and oxidation tests at high temperatures were inconclusive to determine the structure of the thin films, however, the GAXRD analyzes of the samples indicated a reduction in the lattice parameter and an increase in the size of the crystallites, providing greater evidence of the formation of Ti1-xAlxN ternary nitride in all coatings from the replacement of Ti by Al in the TiN structure. The XPS results confirmed the presence of the Ti-Al-N chemical bond from the analysis of the Ti 2p, Al 2p and N 1s regions, confirming the formation of the Ti1-xAlxN solid solution in all deposited samples.